La Sœur-épouse (Genèse 12, 10–20). Edited by Matthieu Arnold, Gilbert Dahan, and Annie Noblesse-Rocher - Evans, Gillian (The journal of theological studies, 2011)
This is an illuminating venture into comparative exegesis. In an elegant little volume, a group of scholars offer discussions of the exegesis in different traditions of the Genesis passages in which, while they are in exile, Sarah, a beautiful and desirable woman, is presented as Abraham’s sister not his wife for fear that if she is known to be his wife, he will be killed. Jan Joosten sets the scene from the point of view of Old Testament scholarship. Marie-Odile Boulnois examines the interpretation of these passages in the Greek patristic tradition, including the view of historians (among them Flavius Josephus) that the conflicting accounts refer to different events.